1987
DOI: 10.1007/bf01412505
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric and optical study of micellar aggregates of sodium taurodeoxycholate

Abstract: Calorimetric measurements, carried out on aqueous solutions of sodium taurodeoxycholate at different NaC1 concentrations, show that the molar heat of dilution decreases with the bile salt concentration and, to a lesser extent, with the NaCI concentration. Circular dichroism spectra, recorded from aqueous solutions of bile salt as a function of concentration, change the sign of the molar ellipticity under 230 nm. 1H NMR spectra show an increase of the half-height line width of the C18 methyl group with the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
3

Year Published

1991
1991
2003
2003

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
1
11
0
3
Order By: Relevance
“…A competing model proposes that the primary interaction is due to the formation of hydrogen bonds between the monomers, leading to interactions between the hydrophilic faces of the bile salt molecules. 19,22,[42][43][44][45][46][47][48] Our earlier work with bile salt aggregates 35,36,39-41 is consistent with the primary/secondary aggregation model, since it was found that hydrophobic guest molecules are located in a hydrophobic and protected environment inside the bile salt aggregates. Singlet excited states have short lifetimes and they cannot relocate before the excited state decays to the ground state.…”
Section: Introductionsupporting
confidence: 78%
“…A competing model proposes that the primary interaction is due to the formation of hydrogen bonds between the monomers, leading to interactions between the hydrophilic faces of the bile salt molecules. 19,22,[42][43][44][45][46][47][48] Our earlier work with bile salt aggregates 35,36,39-41 is consistent with the primary/secondary aggregation model, since it was found that hydrophobic guest molecules are located in a hydrophobic and protected environment inside the bile salt aggregates. Singlet excited states have short lifetimes and they cannot relocate before the excited state decays to the ground state.…”
Section: Introductionsupporting
confidence: 78%
“…Passing from the premicellar to the micellar state, NaCDC, NaDC, and sodium cholate 29 decrease their rotational strength because of aggregation, in contrast with NaTDC. 30 The most interesting feature of the CD spectra is the position of the minima centered at about 202 and 209 nm for NaCDC and NaDC, respectively. The carboxylate and, to a less extent, the carboxylic groups are the chromophores mainly responsible for the absorption and, therefore, are involved in different interactions in the two salts.…”
Section: Resultsmentioning
confidence: 99%
“…The NaCDC molar ellipticity is greater than that of NaDC. Passing from the premicellar to the micellar state, NaCDC, NaDC, and sodium cholate decrease their rotational strength because of aggregation, in contrast with NaTDC . The most interesting feature of the CD spectra is the position of the minima centered at about 202 and 209 nm for NaCDC and NaDC, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The validity of some models was verified by studying aqueous solutions of the micellar aggregates and of their interaction complexes with probe molecules as, for example, bilirubin-IXα (BR) and a spin-labeled cholestane. Small-angle X-ray scattering, nuclear magnetic resonance, , electron spin resonance, EXAFS, and circular dichroism ,,,,, (CD) measurements together with energy calculations 3,10,12,16 were performed. The type of helical structure found in the NaDC and RbDC crystals satisfactorily explains the experimental data of the micellar aggregates. ,,,,, This structure is similar to that of the NaGDC crystal (Figure a).…”
Section: Introductionmentioning
confidence: 99%